Cover Image, Volume 8, Issue 1. Issue 1 (23rd January 2020) - Li, Pao; Huang, Zhao; She, Yin; Qin, Si; Gao, Wanru; Cao, Yanan; Liu, Xia
Abstract : The cover image is based on the ORIGINAL RESEARCH An assessment of the interaction for three Chrysanthemum indicum flavonoids and α‐amylase by surface plasmon resonance by Pao Li et al., https://doi.org/10.1002/fsn3.1349 . Cover Credit: Cover image © Pao Li and Xia Liu Images